Semantic Roles of The Verb “To See” in Javenese of Kertosono - A.A.A Ngr. Adriyanti Weda Ningrat; I Nyoman Kardana; Mirsa Umiyati (Magister of Linguistic, Postgraduated Program, Universitas Warmadewa, 2019)
This study reveals the semantic fields from the